Development and characterization of beef burger added with micronized salt and long-chain n-3 fatty acids - Rios Mera, Juan Dario (2021)
The beef burger is a popular meat product highly appreciated by consumers due to its sensory characteristics. In addition, it offers large intake of proteins, calories, vitamins and minerals. However, the beef burger, and generally meat products, may contain considerable sodium amount from the added salt and an unhealthy lipid profile. These components could increase the risk of metabolic syndrome diseases, such as cardiovascular disease. In this context, the development of healthier meat products is a necessity that responds to the demands of consumers. In this research, a sequential strategy was developed to obtain a beef burger with healthier characteristics. In the first stage, micronized salt was partially mixed with pork fat to protect its structure and used to reduce the salt/sodium content in the product, showing the possibility of reducing 33% of salt in the burger. Thus, texture, yield, physicochemical and sensory characteristics determined by consumers and the overall liking were slightly or not affected. The second step involved the development of an ingredient source of longchain n-3 polyunsaturated fatty acids (eicosapentaenoic, EPA, and docosahexaenoic, DHA) to fortify the beef burger. Microparticles (MP) of soy protein isolate and inulin entrapping fish oil was produced by complex coacervation, obtaining an optimized product in terms of encapsulation efficiency and yield. In addition, MP were resistent to specific conditions of pH and heat treatment, retaining more than 81% of the encapsulated fish oil when transglutaminase was used to give greater resistence to the MP. In the third stage, the strategy of beef burger fortification with fish oil source of EPA and DHA, in combination with the salt/sodium reduction strategy of the first stage was studied. As a result, some differences were found between beef burgers with different salt content (1.5% vs. 1.0%) when unencapsulated or encapsulated fish oil was added, mainly in fatty acids profile and volatile compounds. However, the freezedried MP failed in several quality parameters of beef burger, the most notable being the increase in volatile oxidation compounds, negative sensory profile and overall liking with intermediate score. It is presumed that the large volume occupied by the freezedried MP in the beef burger dough allowed greater access of oxidizing agents during the processing and heat treatment of the product. However, it was possible to obtain a beef burger reduced in salt and fortified with unencapsulated fish oil with good quality characteristics and high overall liking, but that after cooking maintains only EPA. Therefore, a beef burger with healthier and sensorially acceptable characteristics can be obtained, in which the most promising result stands out: the easy adaptation in the industry.